Adherence to the national guidance on foods and drinks to limit or avoid during pregnancy in England: the PEAR Study - Lucy Beasant; Jenny Ingram; Pauline M Emmett; Janet E Cade; Caroline M Taylor (Cambridge University Press, 2024)
Abstract Objective: The National Health Service (NHS) England website provides guidance on foods/drinks to avoid or limit during pregnancy because of microbiological, toxicological or teratogenic hazards. The aims were to determine adherence and whether demographic characteristics were associated with adherence. Design: Cross-sectional study. Setting: Online survey of postpartum women resident in England during pregnancy. Participants: Recently, postpartum women resident in England during their pregnancy (n 598; median age 33 (IQR 30-36) years) completed an online questionnaire (April-November 2022). Questions included those on consumption of twenty-one food/drink items that the NHS advises pregnant women to avoid/limit. The study is part of the Pregnancy, the Environment And nutRition (PEAR) Study. Summary statistics were used to determine proportions adhering to the guidance. Adjusted logistic regression was used to model the associations of adherence with demographic characteristics. Results: Adherence was generally high (>90 % for eight of ten food/drink items to be avoided). However, among pre-pregnancy consumers, several items were not completely avoided, for example, 81 % (128/158) for game meat/gamebirds, 37 % (176/478) for cured meats and 17 % (81/467) for soft cheeses. Greater educational attainment (e.g. caffeinated soft drinks OR 2·25 (95 % CI 1·28, 3·94)), greater maternal age (e.g. oily fish 1·64 (1·05, 2·56)) and lower parity (e.g. caffeinated coffee 0.28 (0.11, 0.69)) were the most usual characteristics associated with adherence. Conclusion: Evidence of concerning levels of non-adherence for some food/drink items suggests a case for more education on some of the guidance, particularly for women with lower educational attainment, greater parity and greater maternal age. Further research on barriers to the implementation of the guidance is needed.